Penerapan Pendekatan Kognitif Behavioral Untuk Membangun Rasa Percaya Diri Pada Anak Di Panti Asuhan Al Washliyah Binjai - Ade Rafiah Addini Awaliyah; Mia Aulina (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Self-confidence is belief in one's abilities, strengths and self-assessment. The problem of lack of self-confidence will hinder his development in socializing, developing his potential, knowing himself, and other developmental tasks. The problem of insecurity is the result of negative thoughts (cognitive distortions) that have an impact on children's behavior. This problem occurred in one of the children at the Al-Washliyah Binjai Orphanage with the initials WS. Through the PKL 1 activity, I tried to help the WS to solve the problem by using the casework method on my mini project. WS. In the intervention process, I used a cognitive-behavioral approach which aims to change negative thoughts about the problems owned by WS into more positive thoughts, so that these thoughts have implications for the attitudes and behaviors taken by WS. After going through various stages of intervention, WS's confidence finally increased. This is a form of success of the mini project that has been implemented.